L’inscription, le masque et la donnée - Gilles Bastin; Jean-Marc Francony (Revue d'anthropologie des connaissances)
This paper deals with the interactions that occur during a research project based on the exploitation of social media data gathered on LinkedIn. Our reflexive approach to what we call the invisible laboratory of the research project allows us to describe the conflicts of interpretations that characterizes those data and the definition of data on the web. The production of our dataset is described as a social process involving the transformation of users “inscriptions” into sociological data. We call this process “datafication” and study the many actors that are involved in it: the sociologist, the IT and web specialist, the LinkedIn user, the social media and the public body in charge of data privacy regulations.